EFFECT OF COLLOIDAL SOLUTIONS OF METAL NANOPARTICLES AND LASER IRRADIATION ON BIOLOGICAL ACTIVITY OF THE EDIBLE MEDICINAL MACROFUNGUS Pleurotus eryngii (PLEUROTACEAE, AGARICALES) IN VITRO - O.B. Mykchaylova; A.M. Negriyko; K.G. Lopatko; N.L. Poyedinok (Biotechnologia Acta)
Aim. The goal of our work was to study the effect of colloidal solutions of metal nanoparticles (NPs) on the synthesis of mycelial mass, polysaccharides, phenolic compounds, and the antioxidant activity of the edible medicinal macrofungus Pleurotus eryngii, as well as the effects of photocatalytic activity of NPs after exposure to low-intensity laser radiation under submerged cultivation conditions.